Pelatihan Pemasaran Digital melalui Pemanfaatan Aplikasi Online Marketplace bagi UMKM di Lapak Berkah PKK Singosari Malang - Habibie Ed Dien; Candra Bella Vista; Wilda Imama Sabilla; Vit Zuraida; Ariadi Retno Tri Hayati Ririd (LPPM Universitas Pendidikan Mandalika (UNDIKMA), 2022)
The purpose of this service activity is to increase knowledge and skills for Micro, Small, and Medium Enterprises (UMKM) actors to be able to do digital marketing through online marketplace applications. The service method uses training with partners, namely the UMKM Blessing PKK in Toyomarto Village, Singosari District, Malang Regency. This service evaluation instrument uses a questionnaire. The data analysis technique used a descriptive technique. The result of this community service shows that the training activities carried out are in accordance with the objectives to be achieved, namely providing an understanding of digital marketing and the ability to use online marketplace applications, so as to optimize product marketing for UMKM actors.